2010
DOI: 10.1007/s00432-010-0918-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 overexpression in human primary squamous cell lung carcinoma is associated with poor patient prognosis

Abstract: Expression patterns of miRNAs were found to be systematically altered in squamous cell lung carcinoma tissue. High miR-21 expression is associated with shortened survival time, indicating that miR-21 may serve as a molecular diagnostic and prognostic marker for patients with squamous cell lung carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
154
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 38 publications
11
154
2
1
Order By: Relevance
“…Treatment on Lovo cells by miR-143 inhibitor could irritate cell proliferation, while the overexpression of miR-143 could restrain cell proliferation. This study proved for the first time that miR-143 could restrain the growth of colon cancer cells by restraining the translation of K-RAS (Gao et al, 2011). Used miRNA chips to examine the non small-cell lung cancer (NSCLC) tissues and found 40 differently expressed miRNAs, where the expression of miR-451 was the lowest and was related to tumor differentiation, pathologic staging, and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Treatment on Lovo cells by miR-143 inhibitor could irritate cell proliferation, while the overexpression of miR-143 could restrain cell proliferation. This study proved for the first time that miR-143 could restrain the growth of colon cancer cells by restraining the translation of K-RAS (Gao et al, 2011). Used miRNA chips to examine the non small-cell lung cancer (NSCLC) tissues and found 40 differently expressed miRNAs, where the expression of miR-451 was the lowest and was related to tumor differentiation, pathologic staging, and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…miRNA with diversified sequences, structure, abundance and expression ways can act as moderator in protein coding mRNA, and is important in gene expression, cell cycle regulation, and individual development. Recently, miRNA expression spectrum disorders were found in various tumors, including gastric cancer (Katada et al, 2009), nasopharyngeal carcinoma (Johnson et al, 2008), breast cancer (Hui et al, 2009), colon cancer (Chen et al, 2009) and lung cancer (Gao et al, 2011) indicating the important role of miRNA in regulation of tumor gene expressions. Because the gene regulation of miRNAs constitutes a powerful network, miRNAs show great potential: as a new treatment target and as a powerful intervention means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that low miR-21 expression was seen by adjuvant treatment in PDAC patients and anti-miR-21 increased anticancer drug activity in vitro. Gao et al [46] indicated that high-level miR-21 in squamous cell lung carcinoma tissue was associated with shortened survival time. On the contrary, Voortman and his colleagues [47] suggested that there was no significant association between the tested microRNAs (miR-21, miR-29b, miR-34a/b/c, miR-155 and let-7a) expression and survival as well as predicted chemotherapy response in resected NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29 plays an indirect role in the inhibition of tumorigenicity through demethylation by DNA methyltransferases DNMT3A and -3B [49]. miR-126 has also been identified as an important inhibitory factor of vascular proliferation via the suppression of vascular epithelial growth factor (VEGF) [50]. Therefore miR-126 is identified as a tumor suppressor because it will be downregulated in cases of lung cancer [51].…”
Section: Tumor Suppressive Mirnas In Lung Cancermentioning
confidence: 99%